PROFESSIONAL BEHAVIOR OF DOCTORS WITH PATIENTS: A FIELD STUDY IN THE CITY OF MEDICINE - Hassan, Ahmed Emad Ali; Rashid, Karar Haidar Falih; Gno, Zain Al-Abidin Kazim Karim; Shebat, Ali Thajeel Atiya (Journal of Medical Genetics and Clinical Biology, 2024)
Through research, we reached the following after the questionnaire forms were distributed to a sample of males and females from the community, which amounted to (50). We entered the answers and sorted them through the statistical program (spss) and obtained several results that we summarize in several points as follows: The study proved that there is a significant relationship between age and suffering from chronic diseases such as blood pressure, diabetes and heart disease, at a rate of 24% for the age of 50 years and over The study proved that there is a significant relationship between education and finding difficulty in reading a prescription written by the doctor, at a rate of 20% equally between the educational level of reading and writing and the educational level of middle school The study proved that there is a significant relationship between the economic status and always resorting to government hospitals, at a rate of 44% for those with an average income The study proved that there is a significant relationship between taking the medicine according to medical instructions and guidelines and the difficulty of reading a prescription written by hand, 54% The study proved that there is a significant relationship between suffering from chronic diseases such as blood pressure, diabetes and heart disease and directing the doctor to do tests before starting the diagnosis, at a rate of 34% The study proved that there is a significant relationship between always resorting to a government hospital and having previously been exposed to a medical error, at a rate of 64% The study proved that there is a significant relationship between feeling that doctors' fees in clinics are high and commitment to periodic examinations, at a rate of 24% The study proved that there is a significant relationship between preferring a doctor with a doctorate over a doctor with a bachelor's degree and commitment to periodic examinations, at a rate of 18% The study proved that there is a significant relationship between preferring an older doctor over a younger doctor and suffering from chronic diseases such as blood pressure, diabetes and heart disease, at a rate of 38% The study proved that there is no relationship between gender, whether male or female, and preferring a doctor with a doctorate over a doctor with a bachelor's degree, at a rate of 24% The study proved that there is no relationship between gender and reading and reviewing the past case before going to the doctor, at a rate of 28%